ANALISIS EFISIENSI PRODUKSI USAHATANI PENANGKAR BAWANG MERAH DI PROVINSI SUMATERA UTARA - Situmorang, Irene; Mardiana, Siti; Zein, Zahari (AGRIBIOS, 2025)
Onion is one of the leading commodities in the agricultural sector in the province of North Sumatra, where the existence of breeder farmer groups is still minimal and requires development efforts in an effort to meet the needs of shallot seeds in North Sumatra Province. The lack of shallot breeder farmer groups indicates that shallot seed breeding is still not in great demand. This study aims to analyse the effect of production factors of land area, seeds, labour, fertilisers and pesticides on the production of shallot seed breeders and analyse the achievement of technical efficiency of shallot seed breeders in North Sumatra Province. This study uses cross section data of 45 sample farmers. Production function analysis using stochastic frontier production function and technical efficiency analysis. The results showed that the production factors of seeds, labour, fertilizers and pesticides had a significant positive effect on the production of shallot seed breeders, while the production factor of land had an insignificant negative effect on the production of shallot seed breeders and shallot seed breeding farms in North Sumatra Province had not yet reached the highest efficiency where the average technical efficiency was 0.8838, In terms of allocative efficiency, the use of production factors of seeds and fertilisers in shallot seed breeding farms in North Sumatra Province has not been efficient and in terms of economic efficiency, the production factors of seeds and fertilisers have not reached the level of economic efficiency.